INFLUENCE OF FERTILIZERS AND GROWTH REGULATOR ON THE CHANGE OF BIOCHEMICAL PROPERTIES OF HYBRIDS OF ONION DURING STORAGE - A. R. Bebris; V. A. Borisov; N. A. Fillrose; S. A. Maslovsky; G. F. Monahos (Овощи России)
Research staff All-Russian Scientific Research Institute of Vegetable Growing – Branch of the Federal State Budgetary Scientific Institution Federal Scientific Vegetable Center in collaboration with Russian state agrarian University – Moscow Timiryazev agricultural Academy conducted research (2014-2016) on the effect of fertilizers and plant growth regulators on changes in the quality of onions of the Pervenets F1, Bennito F1 hybrids and Poisk 012 F1 during storage. As a result of research, the greatest effect was obtained from the complex application of N90P90K90 in combination with trace elements (tenso-cocktail) and a growth regulator Zircon. This system allowed to obtain high biochemical parameters of onions. At the end of the 7 months of storage (October-may), the highest dry matter and sugar content and the minimum nitrate content was observed in Pervenets F1 onions, as well as in hybrid Bennito F1. In the latematuring hybrid onions Poisk 012 F1 at the end of storage, the dry matter content decreased to 6,8-7,3%, sugars to 3,6-4,1%, vitamin "C" to 3,2-4,9 mg%, and nitrates increased to 92,1 mg/kg, which led to a decrease in product quality and large losses of onions from diseases and natural losses (up to 48-59%). The main reason for these losses was the lack of maturity of bulbs,low solids and sugars during harvest. It is obvious that for long-term storage it is necessary to use bulbs with a dry matter content of at least 10%. It was found out that feeding of onions during the beginning of the formation of food organizations with potassium nitrate, treatment with a growth regulator of Zircon and a complex of microelements of tenso-cocktail contributes to better preservation of the quality of onions.